Mechanism of beach erosion at the west of Phu Quoc Island, Southern Vietnam - Tin, Huynh Trung; Nam, Le Hoai; Vinh, Bui Trong (Vietnam Journal of Earth Sciences, 2015)
Phu Quoc Island locates in Gulf of Thailand, Southern Vietnam. Several years ago, due to the effect of climate change and the development ofbeach tourism, beach erosion in the Western beach occurred seriously.ReferencesOceanography monitoring data at Phu Quoc Station from 1979 to 2010, National Institute of Hydrology and Meteorology, Ha Noi March 2011.Duriyapong F. and Nakhapakorn K., 2011. “Coastal vulnerability assessment: a case study of Samut Sakhon coastal zone”, Songklanakarin J.Sci. Technol. 33 (4), p469-476.Krystian W. Pilarczyk, Ryszard B. Zeidler, 1996. Offshore breakwaters and shore evolutioncontrol.Le Hoai Nam, 2013. Coastal erosion at PhuQuoc Island from 1979-2010, Doctoraldissertation, Ho Chi Minh City University ofScience.Nicole Hacking, 1998. Macrofaunalcommunity structure of beaches in northern NewSouth Wales, Australia, Mar. Freshwater Res., 49,page 47-53.Mike 21 User Manual and Mike 21/3FMScientific Reference Manual.http://vi.wikipedia.org/wiki/T%E1%BA%ADp_tin:Phu_quoc_1.jpg